The impact of immediate feedback and leaderboards on cognitive load and vocabulary learning strategies: An SEM approach in online Chinese learning - Song, Yan; Petsangsri, Sirirat; Rattana-Olan, Thanin; Cui, Jianming (Edelweiss Applied Science and Technology, 2026)
The rapid expansion of online education has intensified long-standing challenges related to sustaining learner engagement and managing cognitive resources in virtual classrooms. These challenges are particularly salient in online Chinese vocabulary courses, where learners must acquire and retain a large volume of unfamiliar lexical items. This study disentangles the effects of two specific gamification features, immediate feedback and leaderboards, on cognitive load, vocabulary learning strategies, and vocabulary achievement. Sixty undergraduate students enrolled in an online HSK preparation course were randomly assigned to one of three conditions: immediate feedback, leaderboards, or a non-gamified control group. Over six weeks, participants completed weekly Quizizz-based vocabulary quizzes, a NASA-TLX measure of perceived cognitive load, and a Vocabulary Learning Strategies Questionnaire. Path analysis within a structural equation modeling (SEM) framework revealed that immediate feedback significantly reduced cognitive load and promoted more frequent use of vocabulary learning strategies, which in turn were associated with higher post-test scores. In contrast, leaderboards increased cognitive load while still enhancing strategic vocabulary learning behaviors. The findings extend cognitive load theory and gamification research by clarifying the distinct pathways through which specific game elements influence mental effort and strategic behavior.